2020
DOI: 10.4103/ams.ams_254_19
|View full text |Cite
|
Sign up to set email alerts
|

Removal of displaced maxillary third molar using modified gillie's temporal approach

Abstract: Tooth impaction is a pathological situation where a tooth is unable to achieve its normal functional position within the expected time span. The removal may be associated with intra-operative or post-operative complications. The Le Fort I osteotomy is a procedure used by maxillofacial surgeons to correct a wide range of dentofacial deformities. Due to its versatility and simplicity, it has gained popularity for a wide range of uses. This case report describes the location and surgical removal of a right maxill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Based on the titles and abstracts, 532 studies that did not meet the inclusion criteria were excluded, leaving 34. Subsequently, the full text was obtained and finally 14 papers were included, 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 with a total of 508 patients and 1016 affected teeth extracted, including 508 in the PRF group and 508 in the control group. The risk of bias for the inclusion of RCTs is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the titles and abstracts, 532 studies that did not meet the inclusion criteria were excluded, leaving 34. Subsequently, the full text was obtained and finally 14 papers were included, 5 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 with a total of 508 patients and 1016 affected teeth extracted, including 508 in the PRF group and 508 in the control group. The risk of bias for the inclusion of RCTs is shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Ten 5 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 studies reported VAS scores on postoperative day 7, and 646 affected teeth were finally included: 323 in the PRF group and 323 in the control group. There was a high degree of heterogeneity among the studies ( I 2 = 95%, p < 0.001), so a random‐effects model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…The extra oral approach in first intention seems rather indicated for the teeth projected in high position, as the teeth located in the temporal space. This was done by Paoli et al [20], Elgbouri et al [19] and Shruthi et al [17]. The full coronal approach is reserved for bilateral projections [20].…”
Section: Surgical Approach and Techniquementioning
confidence: 99%
“…The extra oral approach, with an incision at the capillary level also remains very acceptable aesthetically with a scar camouflaged in the hairline, a low morbidity for the modified Gillies incision but more important for the hemicoronal or coronal approach with a risk of injury to the facial nerve and alopecia, atrophy of the temporal muscle [12,17,[19][20][21].…”
Section: Surgical Approach and Techniquementioning
confidence: 99%
See 1 more Smart Citation